Analisis Kelengkapan dan Ketepatan Kodefikasi Penyakit Neoplasma Berdasarkan ICD-10 - Suryandari, Endang Sri Dewi Hastuti; Muttaqien, Anis Nurul Fataya; Gunawan; Sangkot, Hartaty Sarma; Wijaya, Avid (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
Diagnosis coding in neoplasm diseases should be complete and precise in accordance to ICD-10 by providing topography codes and morphology codes. Incompleteness and inaccuracy of codes could have an impact on inaccuracies of morbidity reports and inappropriate treatment, as well as increased medical costs. Preliminary studies at UOBK RSUD Dokter Mohamad Saleh Probolinggo showed the percentage of topography code accuracy in 5 medical record documents (MRDs) for neoplasm diseaes was 100%, and the completeness of the neoplasm diagnosis code was 0%. This study objective was to ascertain the completeness and precision of codes in neoplasm diseases based on ICD-10. The research’s design was a quantitative descriptive study with a retrospective strategy using the population of all MRDs of neoplasm diseases in September-November 2022. The sample of 112 MRDs which taken utilizing the technique of total sampling. The factors in the research was the completeness and accuracy of neoplasm diagnosis codes based on ICD-10. Data were collected through observation in the coding section and checklist sheets. The outcome presented the precision of the topography codes was 90.18%, the precision of the morphology codes was 0%, and the precision and thoroughness of the codes in neoplasm diseases was 0%. The incompleteness and inaccuracy of the codes was caused by the absence of morphological code in the patient's medical resume and errors in selecting the topography code block. Coders should complete the morphological code on the patient's medical resume to obtain the neoplasma diagnosis code’s accuracy and completeness.